CONSERVATIVE ENDODONTICS. PRESENT CONCEPTS AND FUTURE PROPOSITIONS OF MINIMALLY INVASIVE ENDODONTIC TREATMENT: A SYSTEMATIC REVIEW - Suhael Ahmed, Ahmad Hamoud Alsabt, Raghad AlTassan, Hiba Riyadh Talic, Mohannad Abdullah Alghamdi, Wael farhan Alanzi, Faris Qasem Alenzi, Sara Sultan Hussain AlShalawi, Saud Abdulaziz M Albraik, ,Manahil Saleh Almutairi, Shouq Mohammed Aljohani; Abdullah Hussain Aljarullah, Abdulrahman Abdullah S Alomair (Chelonian Research Foundation, 2024)
Residual tissue extent and restoration level significantly influence the survival rate of teeth that have undergone endodontic treatment. The aim of the operator is always conservation of maximum tooth structure. This study aimed to review and assess the utilization of a minimally invasive method throughout all phases of root canal therapy, from initiation to completion. We conducted a comprehensive search in PubMed, Web of Science, and Scopus electronic databases to critically evaluate scientific research on the application of minimally invasive principles in the field of endodontics. The search encompassed the period from 2000 to 2023. Two experts in endodontics conducted the initial electronic search, which yielded a total of 634 publications. We assessed the relevance of the recovered texts' summaries by aligning them with the topic of interest. We excluded any summaries deemed irrelevant. We cannot assert with certainty that minimally invasive treatments should be universally used based on the comprehensive analysis of existing material. Nevertheless, by employing meticulous case selection, minimally invasive treatment has the potential to yield a favorable prognosis while preserving the integrity of the dental structure. Keywords- endodontics, minimal exposure, preserving dentin